Metode Mendongeng Kisah Nabi Dalam Penanaman Moral Anak Usia Dini - Kartini Kartini; Astuti Darmiyanti; Nancy Riana (UIN Sultan Maulana Hasanudin Banten, 2022)
The problem of this research is inappropriate moral behavior that occurs in schools such as: the child doesn’t want to greet the teacher, doesn’t want to share, and still likes to annoy friens. The purpose of this study is to see an overview of instilling religious and moral values into children through the storytelling method of the prophet’s story. This study uses qualitative methods by using data triangulation, with the research subject of group B children in PAUD Miftahul Jannah Rawamerta Karawang. The result of this research is the inculcation of moral values which is carried out through storytelling activities, children’s insight becomes broad, can be motivated, able to distinguish good and bad, able to tell the contents contained in fairy tales, and can answer teacher question, so that chidren’s behavior of children after listening to fairy tales becomes moral and virtuous.